(untitled) (Research, Society and Development, 2020)
Objective: Describe the incidence and clinical-epidemiological profile of gestational syphilis in the northern region of Brazil in the period from 2016 to 2018. Methodology: Descriptive epidemiological study with a quantitative approach, using secondary data required in the Notifiable Diseases Information System (SINAN) of the SUS Computer Department (DATASUS). The numbers of confirmed cases of syphilis in pregnancy in Northern Brazil were used as well as detection rates (per 1,000 live births) corresponding to the 2016-2018 triennium. Results: 14,307 cases of syphilis were reported in pregnant women in the northern region of Brazil between the years 2016 and 2018, with the highest detection rate during the three years of the series in the state of Acre. In addition, the North region has syphilis detection in pregnant women below the national average, occupying the fourth place in the ranking in 2018. Most pregnant women were aged between 20 and 29 years old, schooling from 5th to 8th grade incomplete, with mixed race, were diagnosed in the third trimester of pregnancy, with primary clinical classification and received treatment with penicillin. Conclusion: Syphilis is reported as a reemerging disease, representing a serious public health problem in Brazilian territory, as evidenced by the substantial increase in the number of cases and in the rates of detection of syphilis in pregnant women observed during the three years of study in the region North. Therefore, it becomes substantial to adopt measures to interrupt the transmission chain and reduce the impact of syphilis.